2015
DOI: 10.1080/09291016.2015.1034972
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms and photic entrainment of swimming activity in cave-dwelling fishAstyanax mexicanus(Actinopterygii: Characidae), from El Sotano La Tinaja, San Luis Potosi, Mexico

Abstract: Running title: Circadian rhythms in cave-dwelling fish Astyanax Abstract:Circadian regulation has a profound adaptive meaning in timing the best performance of biological functions in a cyclic niche. However, in cave-dwelling animals (troglobiotic) a lack of photic cyclic environment may represent a disadvantage for persistence of circadian rhythms. There are different populations of cave-dwelling fish Astyanax mexicanus in caves of the Sierra El Abra, Mexico, with different evolutive history. In the present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previous studies in Astyanax have suggested that locomotor activity is controlled by a passive system that can be entrained by exposure to cyclic photic cues (Thines and Wolff-Van Ermengem 1965; Thines and Weyers 1978; Erckens and Martin 1982a; Erckens and Martin 1982b; Duboué et al 2011; Beale et al 2013; Caballero-Hernández et al 2015). This conclusion is further supported by the fact that the results of the present study demonstrate significant rhythms in mean velocity and usage of both the bottom and the top portion of the trial tank in both surface and cavefish under l2:12hr light/dark conditions (LD R –LD T ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in Astyanax have suggested that locomotor activity is controlled by a passive system that can be entrained by exposure to cyclic photic cues (Thines and Wolff-Van Ermengem 1965; Thines and Weyers 1978; Erckens and Martin 1982a; Erckens and Martin 1982b; Duboué et al 2011; Beale et al 2013; Caballero-Hernández et al 2015). This conclusion is further supported by the fact that the results of the present study demonstrate significant rhythms in mean velocity and usage of both the bottom and the top portion of the trial tank in both surface and cavefish under l2:12hr light/dark conditions (LD R –LD T ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing community of researchers, aided by advances in genetic resources, laboratory techniques and assay methods, has shown renewed interest in studying these questions in Astyanax (Romero et al 2003; Espinasa and Jeffery 2006; Yoshizawa and Jeffery 2008), with a dramatic increase in the number of publications on related topics in the last several years (Duboué et al 2011; Duboué et al 2012; Beale et al 2013; Moran et al 2014; Caballero-Hernández et al 2015; Yoshizawa et al 2015; Jaggard et al 2017a; Jaggard et al 2017b). However, before we can fully explore the potential use of this species as a natural model for clinically relevant phenomena, we must refine our understanding of exactly how cave-adapted specimens deviate from normal circadian rhythmicity and how these differences can best be observed and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in adult Mexican cavefish (e.g., Pachón cavefish) there is no circadian locomotor activity during 24 h dark conditions following a 12:12 h light-dark training period (Beale et al, 2013; Moran, Softley & Warrant, 2014). In other independently arisen cave populations (e.g., Tinaja cave population), a weakly trainable circadian clock appears to have been retained, i.e., light-dark cycles make expression levels of circadian clock genes oscillate and these oscillations continue briefly after the removal of the light-dark cycle (∼1 day) (Caballero-Hernández et al, 2015; Carlson & Gross, 2018; Carlson et al, 2018). However, the majority of light-dependent basal locomotor activity seems to be regulated by “masking”, where the ambient light overwrites 24 h-rhythmic circadian behaviors (Rietveld, Minors & Waterhouse, 1993; Caballero-Hernández et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In other independently arisen cave populations (e.g., Tinaja cave population), a weakly trainable circadian clock appears to have been retained, i.e., light-dark cycles make expression levels of circadian clock genes oscillate and these oscillations continue briefly after the removal of the light-dark cycle (∼1 day) (Caballero-Hernández et al, 2015; Carlson & Gross, 2018; Carlson et al, 2018). However, the majority of light-dependent basal locomotor activity seems to be regulated by “masking”, where the ambient light overwrites 24 h-rhythmic circadian behaviors (Rietveld, Minors & Waterhouse, 1993; Caballero-Hernández et al, 2015). The molecular mechanism for masking in fish is largely unknown (but see mouse studies in Panda et al, 2003; Van Gelder, 2003).…”
Section: Introductionmentioning
confidence: 99%